A multifunctional quasi-solid-state polymer electrolyte with highly selective ion highways for practical zinc ion batteries - Chengwu Yang; Pattaraporn Woottapanit; Sining Geng; Rungroj Chanajaree; Yue Shen; Kittima Lolupiman; Wanwisa Limphirat; Teerachote Pakornchote; Thiti Bovornratanaraks; Xinyu Zhang; Jiaqian Qin; Yunhui Huang (Nature Communications)
Abstract The uncontrolled dendrite growth and detrimental parasitic reactions of Zn anodes currently impede the large-scale implementation of aqueous zinc ion batteries. Here, we design a versatile quasi-solid-state polymer electrolyte with highly selective ion transport channels via molecular crosslinking of sodium polyacrylate, lithium magnesium silicate and cellulose nanofiber. The abundant negatively charged ionic channels modulate Zn2+ desolvation process and facilitate ion transport. Moreover, an in-situ formed Zn-Mg-Si medium-entropy alloy on Zn anode allows for an improved Zn nucleation kinetics and homogeneous Zn deposition. These combined advantages of the polymer electrolyte enable Zn anodes to achieve an average Coulombic efficiency of 99.7 % over 2400 cycles and highly reversible cycling up to 600 h with large depth of discharge of 85.6%. The resultant Zn | |V2O5 offers a stable long-term cycling performance and its pouch cell achieves a cycling capacity of 1.13 Ah at industrial-level loading mass of 31.3 mg.